The sexualised use of cannabis among young sexual minority men: "I'm actually enjoying this for the first time". Issue 7 (1st July 2021) - Parent, Natasha; Ferlatte, Olivier; Milloy, M-J; Fast, Danya; Knight, Rod
Abstract: The objective of this study was to identify how cannabis use features within the sexual lives of young sexual minority men who use substances, and how this might intersect with features of their contemporary socio-cultural contexts in a setting where non-medical cannabis was recently legalised: Vancouver, Canada. Forty-one sexual minority men ages 15 to 30 years were recruited between January and December 2018 to participate in in-depth, semi-structured 1-2 h interviews about their experiences of using substances (e.g. cannabis) for sex. Drawing on constant comparative analytic techniques, two themes emerged with regards to participants' perceptions of, and experiences with, the sexualised use of cannabis. First, participants described how they used cannabis for sex to increase sexual pleasure and lower inhibitions. Second, participants described using cannabis for sex to reduce feelings of anxiety and shame, and foster intimacy and connection with sexual partners. These findings identify how the sexualised use of cannabis functions as a 'strategic resource' for sexual minority men to deliberately achieve both physiological and psychoactive effects, while concurrently underscoring the extent to which the contexts, patterns and motivations associated with cannabis use for sex parallel those associated with this form of Chemsex.